Ketamine with and without diazepam or detomidine premedication in bovine paediatric patients - Kandpal, Manjul; Kumar, Amresh (The Indian Journal of Animal Sciences, 2012)
Premedication with atropine @ 0.04 mg/kg im and diazepam @ 1 mg/kg iv or detomidine @ 20 µg/kg im to ketanline @ 12 mg/kg im increased the muscle relaxation and the duration of anaesthesia to 22.15 ± 2.19 and 24.75 ± 2.39 min and complete recovery occurred in 102.00 ± 4.63 and 86.25 ± 3. 19 min, respectively, in calves. A significant increase in heart rate and respiratory rate, decreased tidal volume and increased minute volume was seen after ketamine administration. Surgical anaesthesia could not be produced after atropine-ketamine administration in calves. Diazepam and detomidine counteracted the hypertensive effects of ketamine. ECG changes remained within physiological limits. Haematological and biochemical effects involved a non-significant decrease in PCV, Hb and total erythrocyte count, increase in glucose, serum urea nitrogen and creatinine and insignificant effects on sodium, potassium, chloride and arginase levels. Transient haematological and biochemical changes returned near pre-administration level by 24-48 hr after administration of ketamine.